The Spirit of Boldness : Lessons from the World Bank’s Adolescent Girls Initiative - World Bank Group (World Bank, Washington, DC, 2015)
The adolescent girl’s initiative (AGI) was motivated by the idea that vocational training and youth employment programs tailored to the needs of girls and young women can improve the economic empowerment and agency. By putting that idea into practice in a number of ways, the AGI pilots are making it possible to learn about the demand for such programs and whether in their current form they are a feasible and (in some cases) cost-effective means of meeting their objectives. Adolescent females in lower-income countries face a difficult environment in their path toward economic empowerment, a critical dimension of adulthood. Females, especially from low-income countries, want to participate in programs to support their economic empowerment. Effective programs shared certain features that made it possible for them to reach adolescent girls and young women and successfully assess and impart the skills that they needed.